How Improved Sensitivity of Bioassays and Terminal Half-Life of Drugs Impact on Bioequivalence Trials - Antonio, Marzo; Elena, Fontana (Arzneimittelforschung, 2009)
In planning comparative bioavailability and bioequivalence trials, the half-life of the parent compound and metabolites included in the active moiety requires careful attention. Drugs cleared with long or very long half-lives, mainly in cases of clearance from a deep compartment, could suffer from an inappropriate prevision of the half-life. Prevision of a too short half-life would produce shorter blood sampling and wash-out periods with critical consequences on the extrapolation of AUC to infinity and on a possible carryover effect of the circulating concentration of analytes in the pre-dose sample of the second study period. This problem is further complicated by the evidence that half-lives are influenced by the low limit of quantification of the bioassay method (inverse correlation) and by the blood sampling period (direct correlation). Examples of tamoxifen (CAS 10540-29-1) and its active metabolite desmethyl-tamoxifen and ramipril (CAS 87333-19-5) and its active metabolite ramiprilat are described on the basis of experimental data, focusing on the clearance from a deep compartment occurring with ramiprilat.
Keywords: Bioassay; Bioequivalence; Clearance; Guidelines; Terminal half-life